Regional Variation in the Incidence of Congenital Hypothyroidism in Macedonia - Violeta Anastasovska; Elena Sukarova-Angelovska; Milica Pesevska; Elizabeta Taseva; Mirjana Kocova (MDPI, 2017)
The incidence of congenital hypothyroidism (CH) is increasing in different areas around the world. Potential causes include changes in population ethnic composition, environmental factors, changing screening program methodology and lowering of TSH cutoff levels. The incidence of CH in different regions of Macedonia has not been evaluated before. A total of 251,008 newborns from all eight regions in the country have been screened between 2002 and 2015, by measurement of the thyroid-stimulating hormone (TSH) from blood spots, sampled 48-72 h after birth, using the DELFIA assay. Overall CH incidence confirmed at birth was 1/1976. The highest CH incidence was observed in the Vardar region (1/970), while the Eastern region had the lowest incidence (1/4202; p=0.021). In the other regions, the following CH incidence was detected: Northeastern 1/1459, Pelagonia 1/1627, Polog 1/1444, Skopje 1/2430, Southwestern 1/3226, and Southeastern 1/1843. Interestingly, in the Vardar region, 4.44% of the screened newborns had a TSH concentration > 5 mIU/L, as an indicator of regional iodine deficiency, compared to the Eastern region where 1.66% of newborns had a TSH > 5 mIU/L. The higher CH incidence in some of the regions may be due to increasing exposure to environmental toxic agents and/or deficient iodine intake. Further research into the potential environmental determinants of increased CH risk is warranted.